ANALYSIS OF WHEAT YELLOW RUST MONITORING IN SOUTHERN REGIONS - Oripov Doniyor Makhammadjonovich (European Journal of Agricultural and Rural Education, 2024)
In the article, in order to determine epidemiological areas and monitor rust diseases, using GPS (etrex GARMIN) device, depending on the location of wheat fields, the incidence level and coordinates of the presence or absence of rust diseases at a distance of 25-40 km were determined, and the data was sent to GRRC (Global Rust Reference Center). it was stated that it was filled out based on the form developed by the center